2018
DOI: 10.5194/acp-2018-1092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The unintended consequence of SO<sub>2</sub> and NO<sub>2</sub> regulations over China: increase of ammonia levels and impact on PM<sub>2.5</sub> concentrations

Abstract: <p><strong>Abstract.</strong> Air pollution, reaching hazardous levels in many Chinese cities has been a major concern in China over the past decades. New policies have been applied to regulate anthropogenic pollutant emissions, leading to changes in atmospheric composition and in particulate matter (PM) production. Increasing levels of atmospheric ammonia columns have been observed by satellite during the last years, in particular IASI observations reveal an increase … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…These trends are considered as insignificant everywhere in Europe (except over parts of Albania and Greece, Figure 4b). This demonstrates that the impact of meteorology changes between 2008 and 2015 on NH 3 VCD trends may be weak over Europe, as already shown for other parts of the world (by WichinkKruit et al, [15] for the Netherlands, by Yu et al [16] for the United States, and by Lachatre et al [17] for Eastern China).…”
Section: Strong Increase Of Simulated European Nh 3 Vcdssupporting
confidence: 69%
See 1 more Smart Citation
“…These trends are considered as insignificant everywhere in Europe (except over parts of Albania and Greece, Figure 4b). This demonstrates that the impact of meteorology changes between 2008 and 2015 on NH 3 VCD trends may be weak over Europe, as already shown for other parts of the world (by WichinkKruit et al, [15] for the Netherlands, by Yu et al [16] for the United States, and by Lachatre et al [17] for Eastern China).…”
Section: Strong Increase Of Simulated European Nh 3 Vcdssupporting
confidence: 69%
“…Using satellite observations from the Infrared Atmospheric Sounding Interferometer (IASI, [13]), Van Damme et al [11] also found a significant increase of +1.90 ± 0.43 %/yr over Western and Southern Europe from 2008 to 2018 in the NH 3 VCD. Different reasons have been raised to explain this NH 3 increase in the atmosphere, also observed over other parts of the world [14][15][16][17], including:…”
Section: Introductionmentioning
confidence: 99%
“…This simplified equation between aerosol pH and influencing factors provides a unique tool to predict the pH response to atmospheric processes. For instance, the reduction of particulate sulfate or nitrate without changes in NH x concentration can release more NH 3 into gas phase , to make aerosol pH higher, but this increased amount, judged from , should have an upper limit constrained by the total NH x amount. Calculating the value of each component in and allows the contribution of each influencing factor to pH in different studies to be compared quantitatively, providing a convenient way to compare pH studies in different locations or time periods.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Particles in this size range can penetrate deeply into the respiratory system leading to respiratory and cardio-vascular problems. The formation mechanisms leading to the formation of secondary aerosols, especially the organic fraction, are complex, non-linear and still not fully understood (Bian et al, 2017;Lachatre et al, 2018;Tsigaridis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%